Deformation behavior of TiNi shape-memory alloy under strain- or stress-controlled conditions - Tobushi, H.; Okumara, K.; Endo, M.; Tanaka, K. (Archives of Mechanics, 2002)
The deformation properties of TiNi shape-memory alloy subjected to strain control and stress control were investigated experimentally. The results obtained are summarized as follows. (1) In the case of a full loop, the stress-strain curves under stress-controlled conditions are similar to those under strain-controlled conditions with high strain rate. The overshoot and undershoot do not appear at the start points of the stress-induced martensitic transformation in these curves. (2) In the case of subloop under stress-controlled conditions, temperature decreases and therefore the strain increases owing to the martensitic transformation at the early stage of the unloading process. At the early stage in the reloading process, temperature increases and therefore the strain decreases owing to the reverse transformation. (3) In the case of subloop under stress-controlled conditions, the starting stresses of the martensitic transformation and the reverse transformation in the loading and unloading processes coincide with the transformation stresses under strain-controlled conditions with low strain rate, respectively. (4) The deformation behaviours for a subloop under stress-controlled conditions are prescribed by the condition for progress of the martensitic transformation based on the transformation kinetics. (5) The deformation behaviors subjected to cyclic loading under stress-controlled conditions at constant temperature are also prescribed by the conditions for progress of the martensitic transformation.